ТЕРРАСОВЫЕ РЯДЫ РЕЧНЫХ ДОЛИН СИХОТЭ-АЛИНЯ (УСЛОВИЯ ФОРМИРОВАНИЯ, ВОЗРАСТ И КОРРЕЛЯЦИЯ) ОБЩИЕ УСЛОВИЯ ФОРМИРОВАНИЯ ТЕРРАС И ПРИДОЛИННЫХ УРОВНЕЙ - Короткий А.М. (My University, 2004)
The main factors of river terraces formation are determined. The regional types of river terraces express total rising of the Central Sikhote-Alin (with amplitude up to 300 m) and subsidence of its margins. The local types of terrace sequences have been formed in the coastal zone (under the impact of the sea level changes) within the basalt plateaus and at the places of the river system rearrangement. Tectonic asymmetry of the Sikhote-Alin has resulted in greater erosion cut on the eastern (steep) slope, than on the western (low-angle) one. Relics of Late Miocene river system were revealed among the river valley landforms. Pliocene-Quaternary terrace sequence consists of 7 terraces, which are characterized by subsidence towards Ussury-Khanka depression and coastal zone of the Sea of Japan.
Keywords: Quaternary; Pliocene; Miocene; 551.435.132(282.252); Cenozoic::Quaternary; Кайнозой::Неоген::Плиоцен; Кайнозой::Четвертичная; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene